Inland fisheries in Tamilnadu: A case study of Thiruvannamalai district - Palanichamy, A.P. (International Multidisciplinary Research Journal, 2011)
In a country like India with its undernourished millions the need for enhancing protein rich food cannot be over emphasized. In the context fish production assume great importance. Fish is rich in protein and it is also contains fat in organic substances and vitamins. The protein content on fish ranges from 12 per cent to high as 20 per cent the general beings 17 per cent fisheries contributes 1 percent of the total food supply of world. Thus Per capita fish consumption of India is for below than that of other countries like Taiwan (20kg) Korea (80kg per annum James (1990); Japan (72.0 kg F.A.O 1991. Facroles (85.2 kg) Iceland (92.1 kg)and Portugal (60.02kg). Development o suitable technologies coupled with extension activities has pushed Indian fish production manifold. The marine fisheries potential of the state is estimated at 0.719million tones(0.369 million tones form less than 50 mater depth and 0.35 million tones beyond 50 meters depth) as against the all India potential of 3.934 million tones of the east coast states, Tamil Nadu lands the maximum catch followed by West Bengal.